Influence of thermocycling on shear bond strength of glass ionomer cement to Er:YAG laser‐prepared enamel. Issue 10 (10th December 2015) - Kong, Yuan‐Yuan; Chen, Yi; Shen, Rui; Jiang, Qian‐Zhou; Chen, Min‐Le
Abstract : Purpose: To evaluate the long‐term influence of the shear bond strength (SBS) on glass‐ionomer cement (GIC) to Er:YAG‐irradiated and bur‐prepared enamel. Materials and Methods: One hundred and ninety human premolar and molars were selected and the crowns were sectioned. Samples were divided into five groups, according to surface treatments: bur preparation (B); bur preparation, etching with 37% phosphoric acid (BA); laser preparation (L); laser preparation, etching with 37% phosphoric acid (LA); laser preparation, twice irradiating with laser at low (150 mJ, 10 Hz; water spray 10 ml/min) (LL). Samples were subdivided according to the number of thermo‐cycles (TCs)‐500 TCs, 1, 000 TCs, 3, 000 TCs, and 5, 000 TCs. The SBS between GIC and enamel was measured using a universal testing machine; failure patterns were analyzed with stereomicroscope. The enamel surfaces and the patterns of the junction between GIC and enamel were observed by scanning electronic microscopy (SEM). Results: The SBS of L group was higher than that for the B group ( P < 0.05). The failure mode analysis demonstrated a cohesive failure within the cement in BA and LA groups, but the SBS of LA group was higher than that for the BA group ( P < 0.05). LL had a similar effect on SBS compared with LA. Thirty‐seven percent phosphoric acid had greatly increased SBS of GIC to enamel ( P < 0.05). The SBS was significantly affected by thermocycling (TC) ( P < 0.05). Conclusion: Our results showed that Er:YAG irradiated significantly increased the SBS on GIC to enamel than bur‐prepared enamel. In addition, 37% phosphoric acid pretreated also significantly increased the SBS on GIC to enamel. However, the results of these in vitro tests were limited, and extrapolation to the clinical situation was difficult. Thus, further studies were needed on this subject to simulate the highly complex and dynamic environment in the analysis. Lasers Surg. Med. 48:978–984, 2016. © 2015 Wiley Periodicals, Inc.